Computer Supported Qualitative Research Second International Symposium on Qualitative Research (ISQR 2017) (Advances in Intelligent Systems and Computing,, 2018)
This book includes a selection of the articles accepted for presentation and discussion at the second International Symposium on Qualitative Research (ISQR2017), held in Salamanca, Spain, July 12-14, 2017. ISQR2017 is part of the Iberian-American Congress on Qualitative Research (CIAIQ), and featured four main application fields (Education, Health, Social Sciences, and Engineering and Technology) and seven main subjects: Rationale and Paradigms of Qualitative Research; Systematization of approaches with Qualitative Studies; Qualitative and Mixed Methods Research; Data Analysis Types; Innovative Processes of Qualitative Data Analysis; Qualitative Research in Web Contexts; Qualitative Analysis with the Support of Specific Software. This book is a valuable resource for academics, researchers, teachers and students who need information on the above topics, as well as on the use of Computer Assisted Qualitative Data AnalysiS (CAQDAS). .